Impact of Islamic financial markets on economic growth: evidence from the Middle East and Asia / Nur Hazimah Amran, Wahida Ahmad and Catherine S F Ho - Amran, Nur Hazimah; Ahmad, Wahida; S F Ho, Catherine (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
Globalization and integration of the global financial markets have yielded much volatility in economic activities and it is essential that emerging countries avoid contagious crises to ensure robust development. With the rapid progression in both conventional and Islamic financial markets, countries with dual financial systems have to uphold a stable and resilient financial market that could contribute to sustainable economic growth. This study aimed to investigate the contribution of Islamic financial markets towards economic development in selected Middle Eastern and Asian countries from 2008 to 2017. The study employed panel data analysis methodology on a balanced panel of seven countries and the finding reveals consistent results where both Islamic stock markets and the Islamic banking sector significantly and positively contributed to economic growth. Meanwhile, region significantly interacted in the relationship between Takaful and economic growth positively for Middle Eastern countries but not for Asia. Empirical evidence highlights the importance of the Islamic financial markets in stimulating a nation’s economic growth, which is especially vital for the stock and banking sectors. Further, Asian nations should also further expand and empower the Takaful industry to achieve a positive economic impact.